Chemistry and texture of the rocks at Rocknest, Gale Crater: Evidence for sedimentary origin and diagenetic alteration. Issue 9 (10th September 2014) - Blaney, D. L.; Wiens, R. C.; Maurice, S.; Clegg, S. M.; Anderson, R. B.; Kah, L. C.; Le Mouélic, S.; Ollila, A.; Bridges, N.; Tokar, R.; Berger, G.; Bridges, J. C.; et al.
Abstract A suite of eight rocks analyzed by the Curiosity Rover while it was stopped at the Rocknest sand ripple shows the greatest chemical divergence of any potentially sedimentary rocks analyzed in the early part of the mission. Relative to average Martian soil and to the stratigraphically lower units encountered as part of the Yellowknife Bay formation, these rocks are significantly depleted in MgO, with a mean of 1.3 wt %, and high in Fe, averaging over 20 wt % FeOT, with values between 15 and 26 wt % FeOT. The variable iron and low magnesium and rock texture make it unlikely that these are igneous rocks. Rock surface textures range from rough to smooth, can be pitted or grooved, and show various degrees of wind erosion. Some rocks display poorly defined layering while others seem to show possible fractures. Narrow vertical voids are present in Rocknest 3, one of the rocks showing the strongest layering. Rocks in the vicinity of Rocknest may have undergone some diagenesis similar to other rocks in the Yellowknife Bay Formation as indicated by the presence of soluble calcium phases. The most reasonable scenario is that fine‐grained sediments, potentially a mixture of feldspar‐rich rocks from Bradbury Rise and normal Martian soil, were lithified together by an iron‐rich cement.